Pengetahuan Simbolik Pemuda Hindu Pada Upacara Piodalan Di Kota Palangka Raya - Yeni Lidia Setio Putri; Ni Putu Vidya Ardiyani; I Putu Indra Wangsa; I Nyoman Suandika; I Nyoman Sidi Astawa; Heri Kusuma Tarupay (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
In Hinduism, the Pura Piodalan ceremony is an essential ritual that marks the anniversary of the temple and serves as a form of gratitude and an effort to strengthen spiritual relations with God. The implementation of this ceremony requires the readiness of adequate facilities (upakara) and infrastructure. However, research in Palangka Raya City identified a significant knowledge gap among Hindu youth (aged 18-30 years) regarding the meaning and use of these facilities. This gap is triggered by the dominance of the older generation in ngayah activities (mutual cooperation rituals), the lack of interest of the younger generation in complex rituals due to the influence of the environment and technology, and the lack of encouragement and transfer of knowledge from parents. Although efforts to embrace have been made, active participation is still limited because ngayah is based on sincerity. This condition risks causing dissociation between ritual practice and spiritual understanding, threatening the preservation of Hindu cultural and religious values. Therefore, this study emphasizes the urgency of developing effective strategies, such as increasing involvement in ngayah, relevant education, and the use of modern media, for the sustainability of this tradition